2022
DOI: 10.1093/cid/ciac736
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Findings of Fusobacterium necrophorum or β-Hemolytic Streptococci and Complications in Pharyngotonsillitis—A Registry-Based Study in Southern Sweden

Abstract: Background Most pharyngotonsillitis guidelines focus on the identification of group A streptococci (GAS), guided by clinical scores determining whom to test with a rapid antigen detection test (RADT). Nevertheless, many RADT-negative patients are evaluated for Group C/G streptococci (GCS/GGS) and Fusobacterium necrophorum, yet their importance remains debated. Our primary aim was to evaluate associations between complications and findings of F. necrophorum, GAS or GCS/GGS in pharyngotonsillit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…By highlighting distinctive features of F. necrophorum pharyngotonsillitis in a large number of severely ill cases with pharyngotonsillitis, future guidelines are aided to provide better guidance, with the main predictor being age 13–30 years. Guidelines on management of pharyngotonsillitis might need revision following evidence during the last ten years establishing F. necrophorum as an important cause of pharyngotonsillitis [ 1 , 3 ], peritonsillar abscess [ 4 , 27 ] and with increasing incidence of invasive infections in adolescents and young adults [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By highlighting distinctive features of F. necrophorum pharyngotonsillitis in a large number of severely ill cases with pharyngotonsillitis, future guidelines are aided to provide better guidance, with the main predictor being age 13–30 years. Guidelines on management of pharyngotonsillitis might need revision following evidence during the last ten years establishing F. necrophorum as an important cause of pharyngotonsillitis [ 1 , 3 ], peritonsillar abscess [ 4 , 27 ] and with increasing incidence of invasive infections in adolescents and young adults [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…N/total (%) is presented when any data were missing 1 According to the Charlson comorbidity index [23] 2 21% had missing data. When missing, data was imputed using multiple imputation (25 iterations) with predictive mean matching 3 No randomized controlled trial has investigated antibiotic therapy in F. necrophorum-pharyngotonsillitis. Yet, a Cochrane meta-analysis on antibiotic treatment in pharyngotonsillitis patients with negative cultures for betahaemolytic streptococci have shown symptom reduction following exposure to antibiotics [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that S. dysgalactiae should be considered as a throat pathogen in line with S. pyogenes. In a study of 3,700 AT patients treated in primary health care, Nygren et al found lower complication rates among patients positive for Group C/G streptococci (16%) compared to those positive for S. pyogenes (28%) and F. necrophorum (26%) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, it has been described to be part of the normal tonsillar flora, 1 yet a more accurate description is likely that transient carriage occurs among teenagers and adolescents. 9 F. necrophorum is increasingly recognized as a primary pathogen in local infections, for example, pharyngotonsillitis 10 11 12 13 14 and peritonsillar abscess 15 16 in addition to its role as the typical pathogen seen in Lemierre's syndrome. 1 Little is known of its pathogenicity, including the very particular presentation with thrombosis in Lemierre's syndrome.…”
Section: Introductionmentioning
confidence: 99%